Traffic in Macedonia in the Last Centuries of Turkish Rule (Prilozi za orijentalnu filologiju, 2017)
In the first centuries of the Ottoman rule, Macedonia was covered by a wide netvvork of land routes. The constmction, repairs and maintenance of the roads were first of ali conditioned by war and strategic motives, and then by economic needs. One of the oldest and very important roads until the end of the 18* century was the famous Via Egnatia, connecting Rome to Constantinople, whose route followed the direction of Drač - Elbasan - Struga - Ohrid - Rese - Bitola - Lerin (Florina) - Ostrvo (Arnisa) - Boden (Edesa) - Pela - Solun - Amfipolis - Filipi - Kavala - Enos and at Ipsal on the Maritsa River joined the Constantinople road (Via Militaris) connecting Constantinople with Belgrade and Buda. From the Adriatic coast towards Constantinople, i.e. via the Aegean across Macedonia respectively crossed other roads, too: one road took the direction of Debar - Kičevo - Prilep - Demir Kapija - Dojran - Ser - Sihna - Drama - Kavala, and further along the road Via Egnatia towards Constantinople, and the other via Skadar - Prizren - Skoplje - Kumanovo - Stracin - Kriva Palanka - Djustendil - Samokovo and further along Via Militaris. With the development of trade of the Ottoman Empire with Austria and Russia in the 17th century, great importance was attached to the roads towards the Mediterranean. One fork of this road was Solun - Kukuš - Dojran - Strumica - Radoviš - Štip - Veles - Skoplje - Niš, i.e. Štip - Kumanovo - Niš - Belgrade and further to Pest and Vienna, i.e. Europe. During the lst Serb uprising and so-called Continental blockade, the importance of the old Bosnian-Macedonian road Solun - Kukuš - Dojran - Strumica - Radoviš - Štip - Kumanovo - Priština - Vučitrn - Banjska - Novi Pazar - Sjenica - Prijepolje - Čajniče - Sarajevo and further to Austria and Italy, i.e. to Europe, grew.